A Model For Improving The Management Methodology Of Students Based On Different Management Approaches In Preschool Education. - M.B. Astanakulova (Academia One Publishing, 2024)
Performance management means effective management. Ensuring sustainable high performance applies to all management tasks and the connecting process - communication, decision-making and leadership. It is necessary to look at the enterprise from the point of view of a system consisting of interrelated elements. Elements of the organization and the organization problems due to the fact that they are very interconnected with the external environment easily and quickly solved. Like other organizational problems, the problem of increasing productivity in the future requires a comprehensive approach. Productivity is influenced by various factors of both the external environment and the process of system change. Since these factors influence each other, increasing productivity is not constant
Keywords: productivity; environment; process